1974
DOI: 10.1093/jaoac/57.3.682
|View full text |Cite
|
Sign up to set email alerts
|

Automated Chemical Determination of Methionine

Abstract: A rapid, accurate, and precise spectrophotometry method, based on the nitroprussidemethionine color reaction, has been developed for the determination of methionine in soybeans, mungbeans, and corn. Amino acid interference was eliminated by partial enzymatic hydrolysis of samples for 4 hr at 50 °C with papain; the samples were analyzed by an automated system. Precision and accuracy were determined by repeated independent analyses of 13 samples of corn, mungbeans, and soybeans; the data were compared to indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The reaction was stopped after 10 min with 1.0 mL of 30% acetic acid and the absorbance read at 410 nm. Methionine was determined by the method of Gehrke & Neuner (1974) with some modifications while tryptophan was determined by the procedure developed by De Vries et al. (1980) also with modifications as described below.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was stopped after 10 min with 1.0 mL of 30% acetic acid and the absorbance read at 410 nm. Methionine was determined by the method of Gehrke & Neuner (1974) with some modifications while tryptophan was determined by the procedure developed by De Vries et al. (1980) also with modifications as described below.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent review, Arpiño and Guiochon (1) summarized the current state of the art on this subject. The following approaches have been explored for a direct liquid chromatograph-mass spectrometer (LC-MS) combination: (1) a moving wire/belt system that transports the LC effluent through a series of vacuum locks, where the solvent is evaporated and the sample is then introduced into the ion source for analysis by electron impact ionization (El) or chemical ionization (Cl) (2); (2) a 1% split of the LC effluent into the MS, the LC solvent being used as a Cl reagent gas (3); (3) a vacuum nebulizing interface to introduce the total effluent from a micro LC into the ion source (4); (4) a system that converts the LC effluent into a molecular beam by forcing it through a nozzle restriction followed by flash vaporization using a laser beam (5) or sonic radiation (6) and then MS analysis in the El or Cl mode; (5) the direct vaporization of the total effluent into the MS ion source followed by Cl under atmospheric pressure ionization conditions (API) (7); and ( 6…”
Section: Discussionmentioning
confidence: 99%
“…The classical method for the determination of total methionine involves acid hydrolysis of the protein, and subsequent determination with an amino acid analyzer. The method for the automated determination of methionine after decomposition of the protein has been developed by Gehrke and Neuner (7). However, the reaction with nitroprusside is nonspecific, and cystine causes a rapid fading of the color.…”
Section: Literature Citedmentioning
confidence: 99%
“…Cysteine was added to give concentrations of 125, 250, 500 and 1000 p.p.m. Chemical analyses for free methionine and cysteine (Gehrke & Neuner, 1974) in the cheeses at 1 day old indicated that approximately 50 % of the added amino acids were lost in the whey during pressing. The concentrations of the amino acids in the cheeses were therefore approximately half those added to the curd.…”
Section: Treatment Of Cheesesmentioning
confidence: 99%